文化适应策略 ：中国新移民倾向与新加坡华人的期望 = Acculturation strategies : the acculturation orientations of Chinese new migrants and Singapore Chinese - 黄淑娜 Huang, Linda Shuna (2009)
近年来，移民到新加坡的中国新移民数目显著增加，已经成为一个不能忽视的群体。一个移民到了新的国家，文化适应是他们必须面对的课题之一。他们有着自己对于文化适应的倾向和策略，同时也必须面对移入国主流群体以及其他少数群体对于他们的期望。本文将以互动文化适应模式为理论基础、涉及新移民的事件为重点，以报章报道言论来分析新移民的文化适应倾向，及新加坡华人对于他们的文化适应期望。我们也将分析影响他们倾向的因素，并预测他们的倾向互相影响的成果。New Chinese migrants have increased significantly in recent years, becoming a notable group in Singapore. One of the issues migrants have to face is acculturation. They would have their own acculturation orientation, and the members of the host nations would have acculturation expectations of the new migrants as well. We will analyze the acculturation orientations of the New Chinese migrants and Singapore Chinese, using Interactive Acculturation Model as the theoretical basis. We will also discuss the factors that affect the acculturation orientations, as well as the relational outcome that derives from the acculturation orientations.